Yeast β-glucans and microalgal extracts modulate the immune response and gut microbiome in Senegalese sole (Solea senegalensis) - Carballo, Carlos (2020)
One bottleneck to sustainability of fish aquaculture is the control of infectious diseases. Current trends include the preventive application of immunostimulants and prebiotics such as polysaccharides. The present study investigated how yeast β-glucan (Y), microalgal polysaccharide-enriched extracts (MAe) and whole Phaeodactylum tricornutum cells (MA) modulated the gut microbiome and stimulated the immune system in Senegalese sole (Solea senegalensis) when administered by oral intubation. Blood, intestine and spleen samples were taken at 3 h, 24 h, 48 h and 7 days after treatment. The short-term response (within 48 h after treatment) consisted of up-regulation of il1b and irf7 expression in the gut of the Y treated group. In contrast, administration of MAe decreased expression of tnfa and the chemokine cxc10 in the gut and spleen. Both treatments down-regulated the expression of irf3 with respect to the control group. Lysozyme activity in plasma decreased at 48 h only in the MAe-treated soles. Medium-term response consisted of the up-regulation of clec and irf7 expression in the gut of the Y, MAe and MA groups and of il1b mRNAs in the spleen of the MA group compared to the control group. Microbiome analysis using 16S rDNA gene sequencing indicated that the intestine microbiome was dominated by bacteria of the Vibrio genus (>95%). All the treatments decreased the relative proportion of Vibrio in the microbiome and Y and MAe decreased and MA increased diversity. Quantitative PCR confirmed the load of bacteria of the Vibrio genus was significantly decreased and this was most pronounced in Y treated fish. These data indicate that orally administrated insoluble yeast β-glucans acted locally in the gut modulating the immune response and controlling the Vibrio abundance. In contrast, the MAe slightly reduced the Vibrio load in the intestine and caused a transient systemic anti-inflammatory response. The results indicate that these polysaccharides are a promising source of prebiotics for the sole aquaculture industry.